2008
DOI: 10.1117/12.804678
|View full text |Cite
|
Sign up to set email alerts
|

Model-based sub-resolution assist features using an inverse lithography method

Abstract: The conventional segment-based OPC approach has been applied successfully for many CMOS generations and is currently favored. However, Inverse lithography technology (ILT) is a promising candidate for next-generation optical proximity correction (OPC). Still, there are issues that need to be thoroughly addressed and further optimized. In this work, we propose a model-based pre-OPC flow where the sizing of drawn patterns and placement of surrounding sub-resolution assist features (SRAF) are simultaneously gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…To address this problem, we develop an innovative pixel-flipping algorithm where the pixel-flipping is biased by a wavefront expansion technique. 28 We further incorporate a wavefront-based damping scheme and demonstrate that the resulting masks are similar to those obtained by more elaborated algorithms. For its application as a pre-OPC flow, a single iteration is often sufficient to generate SRAFs and to determine the bias of main features.…”
Section: Introductionsupporting
confidence: 52%
“…To address this problem, we develop an innovative pixel-flipping algorithm where the pixel-flipping is biased by a wavefront expansion technique. 28 We further incorporate a wavefront-based damping scheme and demonstrate that the resulting masks are similar to those obtained by more elaborated algorithms. For its application as a pre-OPC flow, a single iteration is often sufficient to generate SRAFs and to determine the bias of main features.…”
Section: Introductionsupporting
confidence: 52%
“…A few examples of wavefront templates can be found in Ref. [11]. As a result, the indices of boundary pixels end up being the same for individual features.…”
Section: Methodsmentioning
confidence: 97%
“…The generation of the pixel index is adopted from a wavefront expansion technique previously developed by us [11]. For any particular layout, we construct a wavefront from the feature's edges both inwards and outwards.…”
Section: Methodsmentioning
confidence: 99%
“…where I t (r) is the target image as a function of the pixel index r. r is arranged in the radial direction from the geometric center of a drawn pattern, where r 0 is the index of the boundary pixels. The generation of the pixel index is adopted from a wavefront expansion technique previously developed by us [11]. For any particular layout, we construct a wavefront from the feature's edges both inwards and outwards.…”
Section: Methodsmentioning
confidence: 99%
“…Other cost functions, such as edge contours, aerial image contrast, and mask error enhancement factor (MEEF), have also been proposed and can be customized to satisfy strict technological specifications. In our experience, we have observed that given the same cost function and process model, two different optimization algorithms, like a wavefront-based pixel flipping [11], and gradient descent, tend to converge to nearly identical final mask patterns. This phenomenon further highlights the importance of using a favorable cost function.…”
Section: Introductionmentioning
confidence: 99%